Kripke models for intuitionistic propositional logic - Shabana, R; A. Elageili, R. (Libyan Journal of Science &Technology, 2022)
In this paper, we introduce Kripke models for intuitionistic propositional logic showing how these models enable us to understand the intuitionistic point of view to mathematical objects. In addition, we discuss their basic properties and give some applications of them reflecting their importance for intuitionistic propositional logic